Environmental assessment of a building-integrated linear dielectric-based concentrating photovoltaic according to multiple life-cycle indicators. (10th September 2016) - Lamnatou, Chr.; Baig, H.; Chemisana, D.; Mallick, T.K.
Abstract: Building-integrated concentrating photovoltaic (PV) systems are of great interest, offering several advantages for building and environment. The present study is an advancement towards the life cycle assessment (LCA) of a linear dielectric-based building-integrated concentrating PV system by means of multiple life-cycle impact assessment methods and environmental indicators (ReCiPe, Eco-indicator 99, ecological footprint, USEtox, ReCiPe-based and Eco-indicator-99-based payback times (PBTs), etc.), providing a detailed analysis. Two configurations (with and without reflective film) are examined, for different cities (Barcelona, Exeter and Dublin). By focussing on material manufacturing (system with reflective film), in general, ReCiPe (endpoint/single-score; points) results are in accordance to Eco-indicator 99 (single-score; points) findings and based on both methods PVs have the maximum contribution for ecosystems/ecosystem quality and human health. Moreover, based on USEtox results, there is a remarkable difference between the impact of the PVs and the impact of the other components. With regard to the PBTs, taking into account both configurations with/without reflective film, Barcelona presents the lowest ReCiPe and Eco-indicator-99 PBTs ranging from 3.6 to 5.8 years. On the other hand, Exeter and Dublin show PBTs from 3.7 to 7.8 years. According to ReCiPe/endpoint results with characterization, for climate change/human health (system with reflective film) Barcelona shows 1.2 × 10 −7 disability-adjusted-life-years per kWh while Dublin and Exeter present a footprint of present about 1.8 × 10 −7 disability-adjusted-life-years per kWh. Results in terms of (species.yr)/kWh are also presented (ReCiPe/endpoint with characterization), for several scenarios. Regarding the two configurations, the findings based on multiple approaches verify that reflective film considerably improves the eco-profile of the reference system (configuration without reflective film). For example, by utilizing reflective film there is a reduction of ReCiPe-based and Eco-indicator-99-based PBTs ranging from 0.5 to 0.9 years, depending on the scenario. Finally, results from the literature are presented along with results of the present study and a critical discussion is provided. Conclusively, the proposed LCA model can also be applied to similar systems, providing useful information about their environmental profile and offering the possibility to select among different configurations the best from ecological/cleaner production point of view. Highlights: Life-cycle of a building-integrated concentrating photovoltaic is conducted. Multiple life-cycle impact assessment methods and scenarios are adopted. For most of impact categories, photovoltaics/concentrator: the highest footprint. In general, ReCiPe results are in agreement with Eco-indicator 99 findings. Among the studied cities, Barcelona shows the lowest payback times.